Фото- та механокаталітична деградація сафраніну Т в присутності дисперсного ніобату літію - Sydorchuk, V. V.; Khalameida, S. V.; Skubiszewska-Zięba, J.; Leboda, R.; Zazhigalov, O. V.; Davydenko, L. O. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
The influence of hydrothermal and microwave treatments on lithium niobates formation from various reaction mixtures has been studied by the help of XRD and DTA-TG analysis, IR- and UV-Vis spectroscopy. The degradation of safranin in aqueous solutions under UV- and visible irradiation and milling has been investigated. High activity of lithium niobates in this process has been found as dependent on the value of specific surface area of catalyst and the presence of structural defects.